A Reexamination of Li Wenyu's Life and Works - XIAO, Qinghe; GUO, Jianbin (Journal of Research for Christianity in China (JRCC), 2025)
Current scholarly efforts to trace and study the life of Li Wenyu have been limited to commemorative biographical sketches, which lack detail and completeness. There has been no systematic compilation or research on his writings and translations, particularly as scholars differ in their accounts of the number and titles of his works. This paper attempts to synthesize prior research and present a relatively comprehensive and coherent account of Li Wenyu's life. Some scholars have noted that the Jesuit Archives in France hold a diary of his priestly ministry written in Latin. Due to various constraints, the author has not yet accessed this material. Therefore, this chapter's reconstruction of Li Wenyu's life primarily relies on Chinese-language sources. Simultaneously, it examines the number and titles of Li Wenyu's works and writings, analyzes the context and motivations behind his creative output, and lays a foundational material basis for further research into his thought.